Analisis sisa makanan lunak rumah sakit pada penyelenggaraan makanan dengan sistem outsourcing di RSUD Gunung Jati Cirebon - M Agus Ariefuddin; Tjahjono Kuntjoro; Yeni Prawiningdyah (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2009)
Background: An indicator of success in maintaining quality of service in patient nutrition can be measured from leftovers. In average inpatients got soft food as much as 40.1% and about 20.5% of them have leftovers. One benefit of leftover data is that they can be used to evaluate provision of hospital foods. Leftovers indicate that there is a waste in food cost.Objective: To analyze leftovers of hospital soft food in the provision of food using outsourcing system at Gunung Jati Hospital of Cirebon Municipality.Method: This was an observational study that used cross sectional design. Samples were as many as 93 patients. Data were analyzed quantitatively using chi square to identify in factors correlation the presence of leftovers and correlation in respondents’ satisfaction with the quality of food with the presence of leftovers and to identify correlation of irrelevance with leftovers of hospital soft foods portion served with the presence of leftovers. Characteristics of respondents and cost of foods wasted were analyzed using univariate technique.Result: The result of statistical analysis showed that there was significant correlation in sex, level of education, types of diseases and appetite on the presence of leftovers (p < 0.05) and there was no significant correlation based on age and class of hospitalization (p > 0.05). There was no significant correlation in respondents’ satisfaction with quality of foods on the presence of leftovers (p > 0.05). There was significant correlation between irrelevances in the amount of soft food portion served on the presence of leftovers. Total cost foods wasted was Rp 12.559.12/day.Conclusion: There was correlation in sex, level of education, types of diseases and appetite on the presence of leftovers. There was no significant correlation in respondents’ satisfaction with quality of foods on the presence of leftovers (p > 0.05). There was significant correlation between irrelevances in the amount of soft food portion served with leftovers. The cost of foods wasted based on class of hospitalization served greatly varied.